Non-Syndromic Spinal Schwannomas: A Novel Classification - Sun, Ibrahim; Pamir, M. Necmettin (Frontiers in Neurology, 2017)
Schwannomas are the most frequent primary tumors of the spine with an incidence of 0.3 to 0.5/100.000 person per year. Current treatment for non-syndromic spinal schwannomas is total resection of the tumor with preservation of neurovascular structures. This study aims to report neurologic and radiologic outcome following treatment of non-syndromic spinal schwannomas along with a novel tumor classification used in our clinic. A retrospective case series was carried out with a patient sample of 82 male and female patients with non-syndromic spinal schwannomas. All patient data was retrospectively collected from the hospital records. As a routine procedure, after admittance and primary evaluation, patients’ tumors were classified using CT or MRI in accordance with our proposed classification method which employs a dual designation method with tree groups (a,b,c) for tumor volume and four types (I,II,III, IV) for tumor localization. Subsequent resection surgery was followed by neurological assessments and follow up at 45th, 180th and 360th post-operative day. Along with Karnofsky performance status scale, pain, sensory deficits and motor weakness were scored to assess neurologic recovery. Our finding indicate that patients with different tumor types significantly differ in their neurological scores and show consistent but differential neurological recovery at early and late time points post-surgery. Complications during and post-surgery were minimal, occurring only intwo patients. Our findings further reinforces the established safety of total resection operations and indicate that our proposed classification is a simple, effective tool that has proven helpful in preoperative planning and avoiding unnecessary surgical approaches.